2012
DOI: 10.1177/120347541201600505
|View full text |Cite
|
Sign up to set email alerts
|

The Coexistence of Psoriasis and Vitiligo: A review

Abstract: An increase in the expected prevalence of psoriasis in individuals with vitiligo, or vice versa, was not found in our study, suggesting that the coexistence of the two diseases appears to be due to chance alone. Large epidemiologic studies are required to address with certainty whether psoriasis is more common in individuals with vitiligo and vice versa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 42 publications
2
18
1
Order By: Relevance
“… 1 On the other hand, a review of reports on vitiligo and psoriasis from 1968 to 2010 revealed a relatively similar rate of psoriasis in vitiligo patients compared to the rate of psoriasis in general population, suggesting that coexistence of psoriasis and vitiligo is probably due to coincidence. 20 Yet, while the crude prevalence of psoriasis in general population of Korea in our data was 0.3% (data not shown), which is a rate close to the expected prevalence of psoriasis in Korea, 21 the prevalence of psoriasis in vitiligo patients was higher at 1.78% (data not shown).…”
Section: Discussionsupporting
confidence: 59%
“… 1 On the other hand, a review of reports on vitiligo and psoriasis from 1968 to 2010 revealed a relatively similar rate of psoriasis in vitiligo patients compared to the rate of psoriasis in general population, suggesting that coexistence of psoriasis and vitiligo is probably due to coincidence. 20 Yet, while the crude prevalence of psoriasis in general population of Korea in our data was 0.3% (data not shown), which is a rate close to the expected prevalence of psoriasis in Korea, 21 the prevalence of psoriasis in vitiligo patients was higher at 1.78% (data not shown).…”
Section: Discussionsupporting
confidence: 59%
“…Association studies have implicated several genes in susceptibility to both diseases, such as those for the major histocompatibility complex (Mabuchi et al, 2007), TNF-α (Zhuang et al, 2013), protein tyrosine phosphatase non-receptor type 22 (PTPN22) (Song et al, 2013), and cytotoxic T-lymphocyte antigen-4 (CTLA-4) (Muto et al, 2011;Song et al, 2013), which are thought to play important roles in the development of autoimmunity. These genes may, at the least, represent a common affected event in the pathologic processes of psoriasis and vitiligo, although a recent retrospective study failed to find an increased prevalence of psoriasis in individuals with vitiligo, or vice versa (Sawchuk et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…As far as skin ADs were concerned, an OR of 6.8 was detected in the psoriasis group. Vitiligo was the most prevalent condition in the three groups of patients, although its association with psoriasis is still controversial . Alopecia areata resulted to be the second most prevalent skin AD in our cohort.…”
Section: Discussionmentioning
confidence: 74%